SHAKESPEARE AS A PROTOFEMINIST PLAYWRIGHT: A STUDY OF POLITICAL AWARENESS IN GONERILL AND REGAN - Singh, Jai (International Journal of Psychosocial Rehabilitation, 2020)
Calling King Lear, a feminist play is something difficult because many readers will not accept it, because it condemns politically ambitious women i.e. Gonerill and Regan and praises a feminine woman i.e. Cordelia. Apparently, it does not seem to be a feminist play but structure of the play has enough substance to prove it a feminist play. During its presentation, Gonerill and Regan dominate the stage for most of the time they are only second to King Lear as in number of dialogues delivered.King Lear embodies voices of different social groups such as women, illegitimate children, patriarchal ideology, monarchy, faithful servants etc. and the voice of dominant groups seems to succeed. However, it is not the reality because success of various ideologies depends on both their execution in the play and manifestation in the outer society. Portrayal of Gonerill and Regan becomes even more important when we investigate the position and role of women in the England of Elizabethan era. During this period, women were expected to fulfill a variety of domestic roles in society, including roles to serve their husbands and children. Women were supposed to be beautiful, meek, obliging creatures. Literary works reflected and strengthened this social tendency.